The everyday life of a young landowner on the example of the Roman Bniński Junior - Studnicka-Mariańczyk, Karolina; Czerniecka-Haberko, Anna (Biuletyn Historii Wychowania, 2023)
This article has been written based on previously unpublished correspondence of the Bniński family, carried on between August 13, 1876 and May 5, 1890. The sender was Roman Bniński (the father), and the addressee was his son, also Roman. One of the letters was written to his sons Roman and Hilary. This remarkable correspondence allows to recreate daily life of the landed gentry living in Podolia. It also provides an opportunity to look into everyday matters and witness life in Vinnytsia palace. The father’s correspondence with his son enables to recreate aspects of Roman Bniński’s life, his relations with the family members, his attitude towards education, friendships and the forms of spending free time.